The exaggerated inflammatory response in Behçet's syndrome: identification of dysfunctional post-transcriptional regulation of the IFN-γ/CXCL10 IP-10 pathway. (14th July 2015) - Ambrose, N; Khan, E; Ravindran, R; Lightstone, L; Abraham, S; Botto, M; Johns, M; Haskard, D O
Summary: The mechanisms underlying the exaggerated inflammatory response in Behçet's syndrome (BS) remain poorly understood. We investigated the response of CD14 + blood monocytes to interferon (IFN)-γ, focusing on the chemokine CXCL10. Chemokine synthesis and release were analysed at a protein and mRNA level following stimulation with IFN-γ. Findings in BS patients were compared with 25 healthy controls (HC), 15 rheumatoid arthritis (RA) and 15 systemic lupus erythematosus (SLE) disease control patients. BS monocytes produced significantly more CXCL10 protein than HC monocytes from 2 h following IFN-γ stimulation, despite equivalent quantities of mRNA, suggesting more efficient translation. This was significantly more pronounced in BS with high disease activity and in those with ocular and neurological clinical manifestations. The imbalance between CXCL10 protein and mRNA expression was not observed in either RA or SLE patients, and was not seen with other chemokines studied (CXCL9, CXCL11 and CCL2). Furthermore, BS monocytes treated with an alternative stimulant (LPS) did not show abnormal tumour necrosis factor (TNF)-α release. Sucrose density gradients to segregate monocyte CXCL10 mRNA into free RNA or polysome-associated RNA showed equal proportions in BS and HC samples, suggesting that the difference between BS and HC may be due to reduced negative control of CXCL10 translation in BS at a post-initiation level. We conclude that BS monocytes have dysfunctional post-transcriptional regulation of CXCL10 mRNA, resulting in over-expression of CXCL10 protein upon IFN-γ stimulation. As CXCL10 is a chemokine that recruits mononuclear cells, this abnormality may contribute to the exaggerated inflammatory responses that characterizes BS.